An ASD Kids’ Speaking Reaction in Social Media - Nurfahmi, Dzurriyatul Khofifah (Journal of Literature, Linguistics, & Cultural Studies, 2022)
This research examined psycholinguistic analysis of speech responses experienced by autistic people in Special Books by Special Kids YouTube Channel. The aims of this research were to identify the types of responses produced by autistic people, and to analyze how these types of responses were realized by autistic people in Special Books by Special Kids YouTube channel. It is important for us to understand that autistic people were able to respond and understand what other people said because there were still many people who thought that people with autism were people whose words were always considered untrue and could not be fully trusted. It was just because they were more focused on themselves so they had difficulty in getting along with those around them. This research used a descriptive qualitative method with 17 videos as the data sources. The data of this research were responses uttered by autistic people. This study used Rothwell's theory (2000) of autistic response in conversation and Cook’s theory (1971) and Searle's theory (1979) to explain the types of utterances spoken by autistic people in the video. The results of the study indicated the response that appeared the most was the cognitively relevant response from 60 utterances out of 92 data. This proved that autistic people could respond relevantly to the conversation even though they had difficulty in communicating with other people.